PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, LEVERAGE, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Angela Dhea Violinna; Umar Issa Zubaidi (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence regarding to the effect of firm size, firm age, leverage, audit quality, managerial ownership, institutional ownership, growth, and profitability on earnings management. This research was conducted on all non-financial companies listed on the Indonesian stock exchange (IDX) from 2018 to 2020. The method used in sampling is purposive sampling method. The sampling method requires several criteria in sampling. The sample used in this research were 103 non-financial companies that met criteria with a total of 309 data. Hypothesis testing in this research used multiple regression analysis. The results of this research show that audit quality has effect on earnings management, while other variables such as firm size, firm age, leverage, managerial ownership, institutional ownership, growth, and profitability have no effect on earnings management